Watershed Management Programs - Impacts, Sustainability Issues and Policy Development for Enhanced Land Productivity in Semi-Arid Regions of India - Sastry, G.; Reddy, Y.V.R.; Prakash, Om; Venkateswarlu, J. (Journal of Soil and Water Conservation, 2022)
Rainfed agriculture in India is characterized by low productivity, degraded natural resources and widespread poverty. Most of the people living in rural areas depend on agriculture. Many eke their living on the natural resources. Therefore scientists, administrators and policy makers considered development of minted areas / natural resources necessary for improving economic conditions of rural families. Further, it was recognized that this is possible only through a holistic development like the Watershed Development Programme (Sastry et al, 2002).